2000
DOI: 10.1074/jbc.275.2.1414
|View full text |Cite
|
Sign up to set email alerts
|

Stable Transfectants of Smooth Muscle Cell Line Lacking the Expression of Myosin Light Chain Kinase and Their Characterization with Respect to the Actomyosin System

Abstract: We constructed a plasmid vector having a 1.4-kilobase pair insert of myosin light chain kinase (MLCK) cDNA in an antisense direction to express antisense mRNA. The construct was then transfected to SM3, a cell line from vascular smooth muscle cells, producing a few stable transfectants. The down-regulation of MLCK expression in the transfectants was confirmed by both Northern and Western blots. The control SM3 showed chemotaxic motility to platelet-derived growth factor-BB, which was supported by lamellipodia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…The failure to detect changes in MLC phosphorylation is in apparent contradiction to the role of MLC kinase. However, we experienced a similar contradiction when we allowed VSMCs to migrate towards platelet-derived growth factor (PDGF); the extent of MLC phosphorylation was not elevated even if PDGF existed at a concentration sufficient to cause migration (11). MLC kinase regulates myosin of VSMCs not only by its kinase activity but also by its non-kinase activity as reviewed by Gao et al (12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The failure to detect changes in MLC phosphorylation is in apparent contradiction to the role of MLC kinase. However, we experienced a similar contradiction when we allowed VSMCs to migrate towards platelet-derived growth factor (PDGF); the extent of MLC phosphorylation was not elevated even if PDGF existed at a concentration sufficient to cause migration (11). MLC kinase regulates myosin of VSMCs not only by its kinase activity but also by its non-kinase activity as reviewed by Gao et al (12).…”
mentioning
confidence: 99%
“…We cultured GbaSM-4 cells with and without the presence of 6´10 -6 M nicotine; the culture was stopped at various times and processed to detect the phosphorylation using the method described by Kishi et al (11). The extent of phosphorylation expressed as mono-and di-phosphorylated MLC per total MLC was 33.7% in the absence of nicotine and 26.5% -31.6% throughout the treatment of nicotine up to 10 h. Furthermore, neither Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The larger 210-kDa isoform is thought to serve primarily in cytokinesis and cell division and interacts not only with actin but with microtubules as well (5). Down-regulation of the smaller isoform has suggested that this kinase is directly involved in smooth muscle contraction (6,7). In the presence of the Ca 2+ /calmodulin (CaM) complex, MLCK phosphorylates the serine-19 residue of the 20-kDa myosin light chain (MLC), activating myosin ATPase activity with subsequent force development (8).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in our literature survey, we found no reports regarding the roles of MLCK other than its kinase activity in the cytokinesis. Therefore, in order to elucidate the functions of MLCK, we knocked-out the MLCK expression in vascular smooth muscle (VSM) cells of vertebrate origin (5,6). The cultured VSM cells were able to proliferate rapidly in spite of the lack of MLCK.…”
mentioning
confidence: 99%